Dry bones [compact disc, unabridged] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2015)
Wyoming's beloved lawman must solve his coldest case yet when a T. rex skeleton surfaces--along with a dead rancher--in Absaroka County.